Analisis Buku Siswa Kurikulum 2013 Kelas VII SMP Pelajaran Matematika Ditinjau Dari Implementasi Pendekatan Scientific Dan Penilaian Autentik - Muklis, Yoga Muhamad; , Dra. Nining Setyaningsih, M.Si (2015)
This study aimed to analyze whether the students' books curriculum 2013 junior math class VII Semester 1 and Semester 2 is presented in accordance with the implementation of a scientific approach and authentic assessment. This research is a descriptive study with a qualitative approach that preceded the development of analytical instruments suitability of the book in terms of the implementation of a scientific approach and authentic assessment. Descriptions in this research by providing an overview of the contents of the book. The instrument used was a scoring sheet suitability analysis books, as well as suitability analysis instrument validation sheet book. Data collection method used is the method of documentation and observations and interviews to obtain supporting data. The results of the analysis of the suitability of a book with a scientific approach, the book in 2013 curriculum students of class VII semester of junior high school math lesson 1 of 91.875% compatibility with the very good category and the 2nd half of 97.5% with a very good category. The results of the analysis of the suitability of books with authentic assessment, curriculum student book 2013 junior math class VII Semester 1 has the suitability of 93.75% with very good category and the 2nd half of 96.094% with very good category.